Detection of hydrogen peroxide and glucose with a novel fluorescent probe by the enzymatic reaction of amino functionalized MOF nanosheets. Issue 37 (3rd September 2021) - Chen, Jing; Xu, Yali; Xu, Fanghong; Zhang, Qian; Li, Shuying; Lu, Xiaoquan
Abstract : The mechanism for detecting H2 O2 and glucose in the system of the NH2 -MIL-53(Al)-HRP enzymatic reaction. Abstract : Amino-functionalized two-dimensional (2D) MOFs have great potential in biosensors due to their excellent water solubility, high fluorescence, large specific surface area, good adsorption properties and good ability to enrich the target analytes. Fluorescence detection of hydrogen peroxide and glucose mostly relies on monitoring the single fluorescence intensity changes in a single excitation wavelength. Here, a ratiometric fluorescence sensor based on NH2 -MIL-53(Al) nanosheets to sensitively detect H2 O2 and glucose through enzymatic reactions was developed. o -Phenylenediamine (OPD) was oxidized by H2 O2 in the presence of horseradish peroxidase (HRP). Then, the oxidation product could be self-assembled on NH2 -MIL-53(Al) nanosheets by hydrogen bonding and π–π stacking. The orbital interaction or the fluorescence resonance energy transfer (FRET) between the nanosheets and the oxidation product could effectively quench the fluorescence of the nanosheets at 433 nm. At the same time, the oxidation product provided a new emission peak at 564 nm. The fluorescence ratio signal changes generated by this oxidation process were used to stably and sensitively detect H2 O2 and glucose. Structural and mechanistic analysis was carried out by calculation methods such as AICD and ORCA to explore the π electron structure characteristics, the hole/electron orbitals and the quenching phenomenon. The detection limit was 26.9 nM for H2 O2 and 0.041 μM for glucose. The detection of glucose in human serum has a satisfactory recovery of 97.4–102.8%. It is clear that the sensor has a good application prospect in real sample analysis.